Willingness to Pay For Sustainable Green Clothing - Mahnoor Mansoor Khan; Fajar Fatima; Malaika Tariq Ranjha; Sana Akhtar (CV. Literasi Indonesia, 2022)
The study of green sustainable clothing examined willingness to pay for green sustainable clothing. As everything is evolving around us, so does our ecosystem. Our planet earth and climate are disrupted at a very high er rate and their impacts are becoming more serious and harmful with increasing time. The present study was conducted in Punjab Pakistan to determine the willingness to pay for green-sustainable clothing through a questionnaire survey. It was found that the majority of people are showing their willingness to pay for sustainable clothing. According to the questionnaire survey majority of the respondent who belongs to higher income are willing to pay extra Rs 500 for sustainable clothing to improve and promote sustainability. Government must start awareness campaigns for the general public to emphasize the causes and adverse impacts and various impact on socio-economic impacts due to different anthropogenic activities.